Effect of Chelation on Antifungal Activity of Norfloxacin - Choubey, Praveen; Singh, Pramila (Asian Journal of Chemistry, 2010)
Complexes of norfloxacin, an antibiotic drug with some transition elements, have been prepared and evaluated for their antifungal activity. The complexes of Fe(III), Ni(II) and Cu (II) have been characterized on the basis of analytical data, conductance, magnetic susceptibility measurements and spectral data. When complexes were tested for antifungal activity differences were observed between complex and free ligand (drug). The stoichiometry of the complex has been found to be 1 : 2 for Cu(II) where as Ni(II) and Fe(III) complexes show 1 : 1 stoichiometry with chloride or acetate ion in the coordination sphere. The complexes are of the general formulae CuL2.(H2O)2 and MLR (H2O);. [where R = CH3COO– for Ni(II) and Cl– for Fe(III), L = norfloxacin, M = Cu(II), Ni(II), Fe(III)].